ANALISIS HUKUM PEMILIHAN DEKAN FAKULTAS KEDOKTERAN UNSRAT TAHUN 2023 DALAM PERSPEKTIF UNDANG-UNDANG ASN NOMOR 20 TAHUN 2023: Legal Analysis of the 2023 Election of the Dean of the Faculty of Medicine, Unsrat, from the Perspective of the ASN Law Number 20 of 2023 - Mezzaluna Adelya Litty; Primananda, Eko (Faculty of Law, Universitas Trisakti, 2025)
The election of the dean of the Faculty of Medicine, Sam Ratulangi University has a dispute that resulted in a legal debate regarding the implementation of procedures and requirements in the election of positions in state universities. This dispute has issues that are quite interesting, especially in the context of Law Number 20 of 2023 concerning the State Civil Apparatus. The formulation of the problem in this study is What are the legal problems in the election of the dean of the Faculty of Medicine, Sam Ratulangi University? How is the legal analysis of the procedure for selecting the dean of the Faculty of Medicine, Sam Ratulangi University? The method used is normative legal research with a statutory approach and case studies. The results of the discussion and conclusions show that the 2023 ASN Law provides a clear and firm legal basis regarding the requirements for ASN positions, including age requirements in the election of positions in state universities. The dispute was brought to the State Administrative Court and the decision indicated violations committed by the rectorate and one of the candidates for dean elected in the election of the dean of the Faculty of Medicine, Sam Ratulangi University.